THE INSTITUTIONALIZATION OF THE MANAGEMENT SYSTEMS BY TRANSPORT ORGANIZATION IN UKRAINE - I. P. Sadlovska; V. V. Sokolova (Nauka ta progres transportu, 2011)
The manner and matter of construction of control system for an enterprise that wishes to get access to the market of transport services are offered.